To find the value of (x+6)(x+6) = 256, you first need to simplify the left hand side of the equation:

(x+6)(x+6) = x^{2} +6x +6x + 36 = x^{2} + 12x + 36

Substituting this to the original equation will give you this x^{2} + 12x + 36 = 256, which can further be simplified by moving all terms to the left. Doing that will give you the quadratic form (ax^{2} + b^{2} + c = 0) of the equation:

x^{2} + 12x - 220 = 0

Remember that the roots can be obtained by using the quadratic formula given by:

x = [(-b)±√b^{2}-(4ac)] / 2a where a, b, c are the coefficients of the equation. That is, *a* = 1, *b* = 12 and *c* = -220

Substituting the values will give you:

x = [-(12)±√(12)^{2}-(4*1*-220)] / 2(1)

x = [-12±√144-(-880)] / 2

x = [-12±√1024] / 2

x = [-12±32] / 2

First root now equals to:

x = [-12+32] / 2

**x = 10**

Second root:

x = [-12-32] / 2

**x = -22**

There you have it. **The values of x are 10 and -22.**